Legal Analysis Regarding Deed Recognition of Debt which is Followed by Authority to Sell with Guarantee of Land Rights: Case Study of Cassation Voniss Number: 1011/k/Pdt/2014 - Chairul Aman (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
There are relationships that have legal consequences and there are relationships that do not have legal consequences, relationships that have legal consequences give rise to rights and obligations, this makes the law develop rapidly so as well as contract law. In its development, the existing law is accompanied by the progress of reform in the field of law and legislation. The interaction of an increasingly universal society often brings conflicts of law in theory and practice, another result of this interaction is the emergence of various forms of agreements. The description in this journal raises issues that are still unanswered regarding the existence of a Mortgage Agreement Deed (APHT) which then arises or is followed by a Debt Recognition with guaranteed land rights accompanied by the power to sell. This research is classified as a normative research type, namely research on provisions relating to the power to sell on land rights guarantees based on the Deed of Debt Recognition through a juridical analytical descriptive approach. The result of this research is that the Deed of Recognition of Debt with guaranteed land rights followed by a power of attorney to sell basically does not conflict with the provisions of the applicable laws and regulations.